(untitled) - Stretcher, Robert (New Jersey, 2005)
This casebook provides real-world applications addressing the financial decisions that manager's face at entrepreneurial and mid-size companies.
Keywords: Business enterprises,Corporations; Finance,Finance,Case studies; Case studies